Employment motivation and job-related satisfaction: a comparison of police women´s perceptions in Dubai and Taipei - Chu, Doris C. (Policing and society, 2018)
During the past several decades, research on female officers has proliferated. Nevertheless, virtually no studies examine policewomen’s motivations to join law enforcement and their job satisfaction in different metropolitan cities in the global context. Analysing data gathered from 372 female officers (278 from Dubai and 94 from Taipei), this study explores female officers’ motivations to join police forces in Dubai and Taipei. It also compares female officers’ job-related satisfaction (relationships with colleagues and career aspirations) in Dubai and Taipei. While helping others was the top one reason for Dubai officers to join law enforcement, the majority (more than three quarters) of the female officers in Taipei chose to become police officers because of job security. The findings indicated that female officers in Dubai significantly differed from their colleagues in Taipei in several attitudinal dimensions: they showed a higher level of confidence in their work, and they also displayed a higher level of satisfaction with their supervisor, co-workers and careers. Policy implications and suggestions for future research are discussed.